Costa Rica. Media responsibility as a pending issue - Vega Jiménez, Patricia (2021)
The Global Handbook of Media Accountability brings together leading scholars to de-Westernize the academic debate on media accountability and discuss different models of media self-regulation and newsroom transparency around the globe. With examination of the status quo of media accountability in 43 countries worldwide, it offers a theoretically informed comparative analysis of accountability regimes of different varieties. As such, it constitutes the first interdisciplinary academic framework comparing structures of media accountability across all continents and creates an invaluable basis for further research and policymaking. It will therefore appeal to scholars and students of media studies and journalism, mass communication, sociology, and political science, as well as policymakers and practitioners.